The AI for Scientific Discovery Network(+) - Kanza, Samantha (Patterns (N Y), 2021)
The Artificial Intelligence and Augmented Intelligence for Automated Investigation for Scientific Discovery Network(+) (AI3SD) was established in response to the UK Engineering and Physical Sciences Research Council (EPSRC) late-2017 call for a Network(+) to promote cutting-edge research in artificial intelligence to accelerate groundbreaking scientific discoveries. This article provides the philosophical, scientific, and technical underpinnings of the Network(+), the history of the different domains represented in the Network(+), and the specific focus of the Network(+). The activities, collaborations, and research covered in the first year of the Network(+) have highlighted the significant challenges in the chemistry and augmented and artificial intelligence space. These challenges are shaping the future directions of the Network(+). The article concludes with a summary of the lessons learned in running this Network(+) and introduces our plans for the future in a landscape redrawn by COVID-19, including rebranding into the AI 4 Scientific Discovery Network (www.ai4science.network).